1980
DOI: 10.1111/j.1752-0606.1980.tb01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital Role Ideals and Perception of Marital Role Behavior in Distressed and Non Distressed Couples

Abstract: Eighty non-patient couples, 50 couples seeking sex therapy, and 50 couples seeking marital thempy, were asked to report on whom they felt should and who actually does assume responsibility in eight major marital role areas. W n the degree of individual "role strain", that is, the discrepancy between role ideals and role behavior was exumined, the marital therapy patients were found to be experiencing the most role strain. Hwband-w3 discrepancies with respect to who does haw the various role assignments were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The results of the present study suggest that couples' perception and satisfaction with their distribution and satisfaction of sex role behaviors may be an important area of assessment and intervention in conjoint treatment of depression and/or marital distress (cf. Margolin et al, 19831, particularly since role conflict has been identified as a frequent and severe problem area in couples presenting for therapy (Geiss & OLeary, 1981). Although the relationship between marital role behaviors and depression in clinic couples appears largely mediated by marital satisfaction, this finding does not imply that interventions regarding role behaviors may not have an impact on depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study suggest that couples' perception and satisfaction with their distribution and satisfaction of sex role behaviors may be an important area of assessment and intervention in conjoint treatment of depression and/or marital distress (cf. Margolin et al, 19831, particularly since role conflict has been identified as a frequent and severe problem area in couples presenting for therapy (Geiss & OLeary, 1981). Although the relationship between marital role behaviors and depression in clinic couples appears largely mediated by marital satisfaction, this finding does not imply that interventions regarding role behaviors may not have an impact on depression.…”
Section: Discussionmentioning
confidence: 99%
“…While the primary hypotheses of the current study examine the relationship between depression and marital and personality measures of sex roles, we were also interested in the potential mediating impact of marital satisfaction on the phenomenon. That is, since results from past research indicate that marital satisfaction is related to personality-derived measures of sex roles (particularly, femininity) (e.g., Antill, 1983;Baucom & Aiken, 1984;Burger &Jacobson, 1979;House, 1986) as well as to marital roles (e.g., Frank, Anderson & Rubinstein, 1980;Jacob, Kornblith, Anderson & Hartz, 1978;Yogev & Brett, 1985), and since marital distress has been consistently shown to be related to depression (cf. Coyne et al, 19871, any relationship found between marital and personality measures of sex roles and depression may be confounded by the potential mediating influences of marital satisfaction.…”
mentioning
confidence: 99%
“…Considerable research reveals perceptual agreement/ similarity to be associated with relational satisfaction (Frank, Andersen, & Rubinstein, 1980;Laing, Phillipson, & Lee, 1966;Murstein, 1976;White &Hatcher, 1984). In a review of the couple complementary and similarity literature, White and Hatcher (1984) concluded that social/psychological studies and clinical studies repeatedly show satisfied marital partners to be more similar to their spouses than individuals in less satisfied marriages.…”
Section: Perceptual Agreement Versus Expectancy Fulfillmentmentioning
confidence: 99%
“…Changes to socioeconomic factors are also known to present challenges to bipolar partnerships with restrictions in social activities and a fall in family income being noted across several studies (15, 19, 20). However changes in other domains, for example those associated with domestic responsibilities, may also leave partners feeling burdened with responsibilities they would prefer to share and this too may lead to problems in the marital relationship (21).…”
mentioning
confidence: 99%